Variables that dynamize access to information and communication technologies in middle income families from Aburrá Valley - Sandra María López; Ana María Cárdenas Soto; Héctor Alonso Pérez (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
This paper presents the methodology for the selection of the most important or essential variables to access information and communication technologies (ICT) in middle-income families from a developing country. The variables are chosen through a combination of three different methods for the interpretation of the results based on structural analysis using MICMAC (Impact Matrix Cross-reference Multiplication) software.